VD_FINDINFO PPD 13/08 - 14/2012 vom 17. April 2012 - VD Tribunal cantonal (2012)
DIVORCE, PRÉVOYANCE PROFESSIONNELLE, PARTAGESENS GÉNÉRAL, INTÉRÊT MORATOIRE, INTÉRÊT RÉMUNÉRATOIRE | 122 CC, 22 LFLP, 15 al. 2 LPP, 12 OPP2